History of the Middle and Far East in the Studies of Scholars in Lwów (1918-1939) - Pisulińska, Joanna (Anabasis. Studia Classica et Orientalia, 2018)
During the period between the wars (1918-1939), the historians at John Casimir University in Lwów contributed significantly to Polish studies of the Orient, especially to antiquity. The most influential Orientalists in Lwów were Andrzej Gawroński, Zygmunt Smogorzewski, Władysław Kotwicz, and Stefan Stasiak. They created the Institute of Oriental Studies at the University of Lwów, which was open to historians, biblical scholars and archaeologists; they established the Polish Society of Oriental Studies; and they began the first specialized journal on the subject. Their academic output was outstanding, especially in the area of Indian and Mongolian studies, and was appreciated worldwide. Moreover, they inspired and encouraged historians, like Franciszek Bujak and Olgierd Górka, to conduct research into the field. Taken together the older genearation of scholars who studied ancient history (Moses Schorr, Konstanty Chyliński, Aleksy Klawek, Józef Poplicha) and the next (Eugeniusz Słuszkiewicz, Stefan Przeworski, Kazimierz Zakrzewski, Atanazy Fic) expanded the scope of research on the subject, as it is reflected in the curricula offered to the students at the University.